2017
DOI: 10.1103/physrevd.96.063513
|View full text |Cite
|
Sign up to set email alerts
|

Holographic equipartition and the maximization of entropy

Abstract: \begin{abstract} The accelerated expansion of the universe can be interpreted as a tendency to satisfy the holographic equipartition. It can be expressed by a simple law, $\Delta V = \Delta t\left(N_{surf}-\epsilon N_{bulk}\right),$ where $V$ is the Hubble volume in Plank units, $t$ is the cosmic time plank units and $N_{surf/bulk}$ is the degrees of freedom on the horizon/bulk of the universe. We show that this holographic equipartition law effectively implies the maximization of entropy. In the cosmological … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 23 publications
2
44
0
Order By: Relevance
“…Can the expansion of the universe toward a quiescent de Sitter phase be interpreted as thermodynamic equilibration to a maximum-entropy state? It is well established that de Sitter has many of the properties of an equilibrium maximum-entropy state, including a locally thermal density matrix with a constant temperature [21,22], and the relationship between entropy and de Sitter space has been examined from a variety of perspectives [23][24][25][26][27][28][29][30][31].…”
mentioning
confidence: 99%
“…Can the expansion of the universe toward a quiescent de Sitter phase be interpreted as thermodynamic equilibration to a maximum-entropy state? It is well established that de Sitter has many of the properties of an equilibrium maximum-entropy state, including a locally thermal density matrix with a constant temperature [21,22], and the relationship between entropy and de Sitter space has been examined from a variety of perspectives [23][24][25][26][27][28][29][30][31].…”
mentioning
confidence: 99%
“…The Hubble horizon of a de Sitter universe is equivalent to an apparent horizon because the universe is spatially flat. For the thermodynamics of de Sitter universes, see previous works [59][60][61][62][63][64].…”
Section: Horizon Thermodynamics and Holographic Equipartition Lawmentioning
confidence: 99%
“…In addition, the thermodynamics of the Universe has been studied from various viewpoints . In particular, the maximization of entropy has been investigated recently [51][52][53][59][60][61][62][63][64][65], and these studies suggest that our Universe should approach a Λ-dominated universe, namely a de Sitter universe, at least in the last stage, as if our Universe behaves as an ordinary macroscopic system [59]. A de Sitter universe is considered to be in thermal equilibrium based on horizon thermodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In [26] we had suggested that the convenient physical parameter to measure information (or entropy), instead of mass or energy, is the action that usually is considered to be additive like entropy and have a unique discrete value, . In this approach, the maximal entropy (minimal information) principle [37][38][39], is equivalent to the familiar minimal action principle. However, the minimal information principle is more general, especially for quantum descriptions, since in physical equations one can introduce the information entropy terms that correspond to measurement processes.…”
Section: Information-probabilistic Ideamentioning
confidence: 99%